Active Materials - Fratzl, Peter; Friedman, Michael; Krauthausen, Karin; Schäffner, Wolfgang (De Gruyter STEM, 2021)
What is an active material? This book aims to redefine perceptions of the materials that respond to their environment. Through the theory of the structure and functionality of materials found in nature a scientific approach to active materials is first identified. Further interviews with experts from the natural sciences and humanities then seeks to question and redefine this view of materials to create a new definition of active materials.